2007
DOI: 10.1177/1477153507080917
|View full text |Cite
|
Sign up to set email alerts
|

Mesopic visual efficiency I: detection threshold measurements

Abstract: Achromatic thresholds are measured at three sites to investigate the effects of light spectrum on achromatic detection thresholds in the mesopic region. The results of measurements using quasi-monochromatic targets reveal spectral sensitivity functions with two or three peaks, a so-called 'chromatic effect' which is assumed to be due to the influence of the colour-opponent channels. This chromatic contribution seem to be less significant at lower luminances but it is accentuated for peripheral observation. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 22 publications
1
32
0
3
Order By: Relevance
“…54 The mesopic system was derived from two parallel bodies of work, the European MOVE consortium [55][56][57][58] who used and driving on a test track. 62 The mesopic visual response is essentially a weighed combination of the scotopic (S) and photopic (P) responses, and hence the CIE mesopic system 53 provides the weighting factor according to the level of adaptation and the S/P ratio of lighting, this being established by consensus between the two bodies of work.…”
Section: Developments In Science and Technologymentioning
confidence: 99%
“…54 The mesopic system was derived from two parallel bodies of work, the European MOVE consortium [55][56][57][58] who used and driving on a test track. 62 The mesopic visual response is essentially a weighed combination of the scotopic (S) and photopic (P) responses, and hence the CIE mesopic system 53 provides the weighting factor according to the level of adaptation and the S/P ratio of lighting, this being established by consensus between the two bodies of work.…”
Section: Developments In Science and Technologymentioning
confidence: 99%
“…higher rod stimulation) providing improved detection probability and reaction time. 30,[32][33][34][35][36][37][38] In a recent study, a novel apparatus was built with which to measure detection of pavement obstacles under different light sources and illuminances. 9 The results confirmed that obstacle detection increased with increasing illuminance and with higher S/P ratio ( Figure 3).…”
Section: Obstacle Detectionmentioning
confidence: 99%
“…This means that the target luminance was gradually increased until the required task could be carried out, i.e. the target could be detected 3,22 or a specified level of perceived intensity was reached. 21 It is known that the starting point for such an experiment forms an anchor to the response and that if different starting points are used, different results may be obtained.…”
Section: Methods Of Ascending Limitsmentioning
confidence: 99%
“…This experiment considers variations in target luminance but not size, measuring contrast threshold using the method of ascending limits as used in recent studies. 3,21,22 The independent variables were target position, position of an extraneous light source and glare; the dependent variable was contrast threshold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation